Study on mechanical properties of rare earth elements modified high carbon chromium bearing steel. (March 2023) - Zhao, Qiancheng; Luo, Hong; Pan, Zhimin; Wang, Xuefei; Cheng, Hongxu
Abstract: The microstructure and mechanical properties of rare earth (RE) elements (La, Ce) modified GCr15 bearing steel were studied by electron backscattered diffraction measurements, Vickers hardness, tensile tests, compressive tests, Charpy impact tests, and the rotating bending fatigue measurements. Results showed that RE elements refined the average grain size of GCr15 bearing steel. The relative mechanical properties, such as tensile strength, compressive strength, and fatigue strength were enhanced. Furthermore, the effect of RE elements on the size and chemical composition of inclusions in GCr15 bearing steel was also discussed. Graphical Abstract: ga1